Climate Change Impact on Archipelagic State: The Beginning of Indonesia’s Territorial Maritime Extinction? - Amanda Christie (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Climate change is a global challenge that is becoming more urgent for countries around the world to anticipate its negative impacts. Especially for archipelagic countries, including Indonesia, the impact of climate change such as rising sea levels cannot be underestimated because it leads to sovereignty issues. In the context of sovereignty, this research tries to analyze the impact of climate change on Indonesia's national sovereignty in relation to international law by focusing on three main topics, namely the perspective of international law on a country's maritime territory, the impact of climate change on Indonesia's sovereignty, and actions that can be taken to avoid the negative effects of climate change. The conclusion of this research shows that Indonesia is facing complex legal challenges in dealing with the impacts of climate change where international law has not provided arrangements related to the sovereignty of archipelagic states if climate change causes the islands that are part of the country to sink. However, advocating for the application of the principle of baseline permanence can help Indonesia protect its maritime interests in the midst of global climate change.